Suicidal tendencies and psychiatric symptoms as consequence of anabolic androgenic steroid usage among athletes in District Rawalpindi - Basharat Hussain; Muhammad Tahir Khalily; Muhammad Athar Khalily (Journal of the Pakistan Medical Association, 2022)
Objective: To elucidate the possible association between suicidal tendencies and psychiatric symptoms associated with anabolic androgenic steroid usage among athletes. Method: The cross-sectional study was conducted from December 2016 to July 2017 in Rawalpini and Wah Canttonment, Pakistan, after approval from the International Islamic University, Islamabad, and comprised male athletes aged >18 years. Those using androgenic anabolic steroid formed group A, while the non-users were in group B. In addition to demographis, data was collected using Beck Scale for Suicidal Ideation and the Symptoms Checklist-90. Data was analysed using SPSS 22. ---Continue